Trauma Centers and Acute Care Surgery A Novel Organizational and Cultural Model - Chiara, Osvaldo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book offers an overview of acute care surgery around the world, focusing on the four main branches of this novel subdiscipline: trauma, general emergencies, critical care, and rescue surgery. The book$1 (Bs primary goal is to provide a general view of acute care surgery, while addressing the most important issues in depth. The content is divided into three parts, the first of which is dedicated to the general organization of trauma centers, including the composition of modern trauma teams. Protocols of activation and action for the trauma team, as well as damage control procedures both in the emergency room and in the surgical theatre, are described. The book also addresses the development of a trauma registry, together with the quality assessment process that can be applied. In turn, the second part describes the principal protocols for making diagnoses, with special attention to circumstances such as unstable hemodynamics, neurological deterioration, normal vital signs, and penetrating injuries. The book subsequently deals with the most important aspects of trauma to the abdomen, chest, and pelvis, with notes on both surgical and intensive care issues. Practical descriptions of how to treat principal injuries to various organs are also provided. Finally, the third part of the book is dedicated to the most frequent general surgical emergencies and rescue surgical approaches, and includes information on diagnostic support with point of care ultrasound and endoscopic advanced techniques. Presenting cutting-edge strategies, this book will be of interest to professionals involved in surgical and intensive care for emergency conditions, such as colonic perforations, obstructions, acute pancreatitis, biliary tree stones, and caustic injuries.s
1 The tale of two cities: the development of trauma and acute care surgery -- 2 Organization and training in trauma and acute care surgery in Italy -- 3 The development of a regional trauma registry -- 4 Quality assessment in acute care surgery -- 5 Diagnostic protocols in trauma care -- 6 Damage control surgery. An Update -- 7 Damage control resuscitation and massive transfusion -- 8 REBOA in exanguinating torso haemorrhage -- 9 Definitive Care of abdominal solid organ injuries -- 10 Trauma to the chest: the role of trauma surgeon -- 11 Abdomino-pelvic trauma -- 12 The open abdomen: indications and techniques -- 13 Entero-atmospheric fistula: a challenge of acute care surgery -- 14 Operative endoscopy in acute care surgery -- 15 Point of Care Ultrasounds in acute care surgery -- 16 Large bowel emergencies -- 17 Biliary emergencies -- 18 Step-up approach in acute pancreatitis -- 19 Source control in abdominal sepsis -- 20 Laparoscopy in acute care surgery -- 21 Caustic injuries.
Keywords: Surgery; Emergency medicine; Anesthesiology; Critical care medicine; Nursing; General Surgery; Emergency Medicine; Anesthesiology; Intensive Care Medicine; Nursing; Surgical Procedures, Operative; Emergency Treatment; Critical Care; Trauma Centers; Models, Organizational